2002
DOI: 10.1243/095440802321194503
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of two-phase flow patterns with the use of dynamic image analysis

Abstract: This research work aimed at developing techniques for the recognition of two-phase ow patterns using image analysis. Flow was realized in a at rectangular channel. Information recorded with a CCD camera, was analysed using the authors' own software. The change in the grey level value from the recorded ow realizations was investigated. The results of this analysis allowed identi cation of the twophase ow structures obtained. Stochastic analysis of the uidization process was also carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…It was demonstrated that different two-phase flow regimes can occur under identical flow conditions, yet, under the condition that other types of gas distribution systems are used. Similar results are reported in other papers [26,41,42]. This fact confirms the considerable effect of the gas phase distributor on two-phase flow regimes.…”
Section: Resultssupporting
confidence: 92%
“…It was demonstrated that different two-phase flow regimes can occur under identical flow conditions, yet, under the condition that other types of gas distribution systems are used. Similar results are reported in other papers [26,41,42]. This fact confirms the considerable effect of the gas phase distributor on two-phase flow regimes.…”
Section: Resultssupporting
confidence: 92%
“…After then, to identify flow regime some image processing algorithm such as watershed segmentation, top-hat filtering and H-minima transform etc. can be applied [146,7]. The processing allows determining the bubble velocity, shape, length and frequency with the standard error of 7%.…”
Section: Flow Regime Identificationmentioning
confidence: 99%
“…The mechanism for converting this energy takes place in a multiphase systems in wastewater and in a systems inside the HP. Currently, many studies are carried out to increase the efficiency of these processes and intensify the collection of heat from heat exchangers [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%